2017
DOI: 10.35790/ebm.5.2.2017.18602
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Berhubungan dengan Kadar Hemoglobin pada Ibu Hamil di Puskesmas Lolak

Abstract: The first 1000 days of early life nutrition is the golden period of growth and development that does not occur in other age groups. During pregnancy, energy needs and nutrient intake have to be improved. Inadequate nutrition and some factors that influence hemoglobin level in this period may increase the risk for both mother and fetus. This study was aimed to determine the factors associated with hemoglobin levels among pregnant women at Lolak Primary Health Center. This was an analytical study with a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…This study is in line with research conducted by Wiraprasidi et al [20] where pregnant women who suffer from anemia with abnormal hemoglobin levels were found to be 94.1%. Previous research conducted by Sugiarsih and Wariyah (21) also found that pregnant women suffering from anemia with abnormal hemoglobin levels were 54.6%.…”
Section: Hemoglobin Levels Of Pregnant Womensupporting
confidence: 93%
“…This study is in line with research conducted by Wiraprasidi et al [20] where pregnant women who suffer from anemia with abnormal hemoglobin levels were found to be 94.1%. Previous research conducted by Sugiarsih and Wariyah (21) also found that pregnant women suffering from anemia with abnormal hemoglobin levels were 54.6%.…”
Section: Hemoglobin Levels Of Pregnant Womensupporting
confidence: 93%
“…The increase of blood lipid profile of broiler in this present study may be related with the essential fatty acid content in candlenut powder. Previously, Wiraprasidi et al, (2017) explained that essential fatty acid had crucial role to support red blood cell formation. For that reason, the increase of candlenut supplementation in the diet may increase essential fatty acid intake and consequently could increase blood profile.…”
Section: Resultsmentioning
confidence: 99%
“…32 Another study by Wiraprasidi et al at Lolak Public Health Centre also reported similar findings; there was an insignificant association between hemoglobin level and MUAC. 34…”
Section: The Difference Of Haemoglobin Level Between Santriwati With and Without Risk Of Cedmentioning
confidence: 99%